2020
DOI: 10.1101/2020.04.24.20070169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Role of Personal Protective Equipment Use in the Protection Against COVID-19 Infection Among Health Care Workers

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has posed a major challenge for protecting health care workers (HCWs) against the infection. Use of personal protective equipment (PPE) in health care workplace is recommended as a high priority. In order to investigate the relationship between PPE use and the number of COVID-19 cases among HCWs, we conducted a molecular epidemiological study among 142 HCWs who were dispatched from Hefei to work in Wuhan and 284 HCWs who remained in Hefei, China; both provided c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
3
8
0
4
Order By: Relevance
“…The authors’ findings are encouraging, and in line with a recent preprint study from Hefei and Wuhan that also reported that none of 426 frontline healthcare workers provided with appropriate access to PPE contracted covid-19 5. These studies underscore that adequate training and uninterrupted availability of sufficient, adequate PPE protects healthcare workers from harm, and such provision remains critical to their safety during a pandemic likely to continue for the foreseeable future.…”
supporting
confidence: 72%
“…The authors’ findings are encouraging, and in line with a recent preprint study from Hefei and Wuhan that also reported that none of 426 frontline healthcare workers provided with appropriate access to PPE contracted covid-19 5. These studies underscore that adequate training and uninterrupted availability of sufficient, adequate PPE protects healthcare workers from harm, and such provision remains critical to their safety during a pandemic likely to continue for the foreseeable future.…”
supporting
confidence: 72%
“…Lack of appropriate PPE itself can put the HCPs at risk of contracting the virus and infecting other healthcare workers and their family. Although this problem did not only exist in Ethiopia, it was also reported from China [18] and other countries. In one study in Jordan, only 18.5% of frontline doctors reported that all PPE were available and most shortage was reported in protective facemasks [19].…”
Section: Discussionmentioning
confidence: 95%
“…Protection against infection with SARS-CoV-2 has been demonstrated in health care workers with the use of PPE. 22 , 23 …”
Section: Recommendationsmentioning
confidence: 99%